Financial Performance On Firm Value Mediated By Islamic Performance At Islamic Commercial Banks In Indonesia - Gn Qoda'ah; Abdurrahman Abdurrahman (LPPM ISNJ Bengkalis, 2023)
This research aims to prove the influence of financial performance on company value, which is mediated by Islamic performance. The method used is panel data regression and path analysis using secondary data from Islamic commercial bank's (ICBs) annual reports in Indonesia. The population in this research is ICBs in Indonesia registered with the Financial Services Authority (FSA) in 2017-2021, totaling 14 ICBs. The sampling technique uses purposive sampling to obtain a sample of 10 ICBs. The research results prove that return on assets (ROA) and capital adequacy ratio (CAR) partially have a positive effect on the sharia maqashid index (SMI). Operational cost operational income (OCOI) partially does not affect SMI and firm value. CAR and SMI partially have a positive effect on firm value. ROA partially does not affect firm value. SMI can mediate the influence of ROA and CAR on firm value, but SMI cannot mediate the influence of OCOI on firm value. This research can complement existing theories and be a reference for Islamic banking in improving the implementation of SMI indicators and for the government in designing Islamic banking performance measurement models integrated with SMI indicators.